A Perspective View on Knowledge Management with Business Strategy - Gopal, C. S. Ramani; Joy, P.A. (Gyan Management Journal, 2011)
Knowledge Management is an emerging term currently used in organizations which recognize the need to make more effective use of their human and IT resources. The relationship between the strategic direction of a business and its strategic approach to knowledge management, assumes that there exists collective organizational knowledge that can be managed to encourage the realization of business goals. The strategic approach to organizational knowledge management will no doubt include the management knowledge at the levels of individual's boundary from customers, suppliers and competitors. However, as business strategy is usual driven from the senor organizational executive, this paper will focus on knowledge management from a strategic organizational perspective. Knowledge Management and Business strategy must drive each other with balance. Since creativity with strategy is called good design, establish a link between them. While devising this link and using it as a basis for Knowledge Management System, some points need attention, i.e. Any effective Knowledge Management strategy should starts with a vision. Knowledge drives strategy and Strategy drives Knowledge Management. By preparing a series of well defined iterative steps, interpret it into low level strategic steps and Knowledge Management system functionalities. After identifying the key characteristics that are needed in a Knowledge Management system, it should be aligned successfully with business strategy.
Keywords: Knowledge Management; Business Strategy; KM System